2018
DOI: 10.1103/physrevd.97.094028
|View full text |Cite
|
Sign up to set email alerts
|

NNLO QCD corrections to production of a spin-2 particle with nonuniversal couplings in the Drell-Yan process

Abstract: We study the phenomenological impact of the interaction of spin-2 fields with those of the Standard Model in a model independent framework up to next-to-next-to-leading order in perturbative quantum chromodynamics. We use the invariant mass distribution of the pair of leptons produced at the Large Hadron Collider to demonstrate this. A minimal scenario where the spin-2 fields couple to two gauge invariant operators with different coupling strengths has been considered. These operators not being conserved show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…5] are computed. The details of computational procedure can be found in [57,58]. Beyond the leading order (LO), the partonic channels consists of one-and two-loop virtual subprocesses, realvirtual and single and double-real emissions, some of which are presented in Figs.…”
Section: A Methodologymentioning
confidence: 99%
“…5] are computed. The details of computational procedure can be found in [57,58]. Beyond the leading order (LO), the partonic channels consists of one-and two-loop virtual subprocesses, realvirtual and single and double-real emissions, some of which are presented in Figs.…”
Section: A Methodologymentioning
confidence: 99%
“…There it has been found that the NNLO correction changes the cross-section by 21% over NLO results and constrains the scale uncertainty to 1.6%. Similar accuracy is also available for non-universal spin-2 production [82] where spin-2 couples with different coupling to the SM fields. The first attempt in calculating the SV corrections beyond NNLO can be seen [83] in the context of ADD model in DY invariant mass distribution after the completion of three-loop quark and gluon form factor [84].…”
Section: Introductionmentioning
confidence: 92%
“…This necessitates further higher order QCD corrections for this model. The first complete next-to-next-to leading order (NNLO) computation has been performed [15] in the dilepton channel. A detailed analysis has been presented there along with the comparison with universal scenario.…”
Section: Jhep04(2021)111mentioning
confidence: 99%
“…All the relevant anomalous dimensions (γ IJ ) are extracted to three loops [15] from the bare quark and gluon form factors and by simply claiming the universality of the infrared divergences at the same order. For the sake of completeness we have collected those in the appendix A.…”
Section: Jhep04(2021)111mentioning
confidence: 99%